Fishbone Diagram Analysis in the Implementation of Integrated Management of Childhood Illness (IMCI) in Indonesia - Dwi Octa Amalia; Sabarinah Sabarinah (Universitas Aisyah Pringsewu, 2023)
Integrated Management of Childhood Illness (IMCI) is an integrated and comprehensive approach to health service that focuses on reducing morbidity and mortality under-five children. This study aims to get an overview of IMCI implementation in Indonesia. The research uses a literature review method using a qualitative approach analysis, through a fishbone diagram that includes man, method, machine, material, and money. Articles were searched through databases like Google Scholar, Proquest, Scopus, Science Direct, Biomed Central, and Pubmed, with publication years 2016-2022. The challenges in implementing IMCI reported from the 8 articles were lack of training for IMCI officers; low compliance in both IMCI management and form filling; lack of support including supervision from the health office, financial, facilities, and infrastructure. The percentage coverage of puskesmas that implemented IMCI is quite good. However, there are still many under-five children whom IMCI has not served and its implementation has not been under IMCI guidelines. To improve the IMCI quality, it is necessary to conduct training and regular orientation as well as on-the-job training, supervision, monitoring and evaluation both internally and from the local health office periodically, provision of a support system includes facilities and infrastructure, medicine, and medical consumables. Abstrak: Manajemen Terpadu Balita Sakit (MTBS) merupakan pendekatan komprehensif dan terintegrasi dalam pelayanan balita sakit yang berfokus untuk menurunkan kesakitan dan kematian pada balita. Tujuan penelitian adalah untuk mendapatkan gambaran implementasi MTBS di puskesmas di Indonesia. Penelitian menggunakan metode literature review melalui pendekatan kualitatif fishbone diagram dengan menganalisis komponen man, methode, machine, materials, and money. Penelusuran artikel melalui database Google Scholar, Proquest, Scopus, Science Direct, Biomed Central, and Pubmed yang terbit tahun 2016-2022. Dari 8 artikel yang direview menunjukkan masih kurangnya petugas MTBS terlatih; rendahnya kepatuhan petugas dalam tata laksana dan kelengkapan pengisian formulir MTBS; kuranganya dukungan dalam hal supervisi dari dinas kesehatan, dukungan dana, sarana dan prasarana. Pelayanan MTBS belum dilaksanakan secara optimal, meskipun cakupan puskesmas MTBS yang melaksanakan MTBS sudah cukup baik. Namun masih banyak balita sakit yang belum dilayani MTBS dan pelayanan belum sesuai dengan standar pedoman MTBS. Untuk meningkatkan kualitas pelayanan MTBS, perlu dilakukan pelatihan dan orientasi bagi petugas MTBS termasuk on-the-job training (kalakarya MTBS) di puskesmas, peningkatan supervisi fasilitatif, monitoring dan evaluasi secara berkala baik di internal puskesmas ataupun dari dinas kesehatan, penyediaan sarana dan prasarana penunjang, serta obat-obatan dan bahan medis habis pakai.